2008
DOI: 10.1038/pcan.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy for advanced prostate cancer bleeding

Abstract: Advanced prostate cancer patients frequently deal with intractable prostatic bleeding which is a difficult problem to manage. Intraurethral high-dose rate (HDR) brachytherapy may palliate this condition. Advanced prostate cancer patients with intractable prostatic bleeding were offered brachytherapy with Iridium-192 using a Micro-selectron HDR machine. During a 5-year period, analysis was performed in 23 patients with a median age and Gleason score of 78 years and 9, respectively. Following brachytherapy, haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…94 Additional epiphenomena of the Trousseau's syndrome have been identified to follow prostate cancer, including superior vena cava syndrome caused by an intravascular thrombosis, 95 mesenteric venous thrombosis, 96 central retinal vein occlusion, 97 and transverse venous sinus obstruction. 98 Despite hypercoagulability manifested by venous and arterial thrombosis having been documented in several large clinical trials in prostate cancer patients, many investigators have conversely reported a high risk of intractable prostatic bleeding 99 and postoperative bleeding, 100 the pathogenesis of which is still mostly unknown. Occasionally, development of acquired inhibitors to factor VIII has also been reported in patients with either prostate cancer [101][102][103] or adenoma.…”
Section: Disorders Of Hemostasis In Prostate Cancermentioning
confidence: 99%
“…94 Additional epiphenomena of the Trousseau's syndrome have been identified to follow prostate cancer, including superior vena cava syndrome caused by an intravascular thrombosis, 95 mesenteric venous thrombosis, 96 central retinal vein occlusion, 97 and transverse venous sinus obstruction. 98 Despite hypercoagulability manifested by venous and arterial thrombosis having been documented in several large clinical trials in prostate cancer patients, many investigators have conversely reported a high risk of intractable prostatic bleeding 99 and postoperative bleeding, 100 the pathogenesis of which is still mostly unknown. Occasionally, development of acquired inhibitors to factor VIII has also been reported in patients with either prostate cancer [101][102][103] or adenoma.…”
Section: Disorders Of Hemostasis In Prostate Cancermentioning
confidence: 99%